Engineering Fluid Mechanics - Yamaguchi, H. (Fluid Mechanics and Its Applications,, 2008)
This book is intended for advanced engineering students in university or college and could serve as a reference for practical engineers. In recent years the development of fluid machineries has required a wider range of study in order to achieve a new level of developmental and conceptual progress. The field of fluid engineering is quite diverse in the sense that so many variations of flow exist in fluid machinery or an installation, whose characteristics are wholly dependent upon the flow field which is det- mined by the function of the machine setting itself. One who is studying fluid engineering, for the purpose of gaining a working knowledge of fluid machineries and their relevant installations, must understand not only the type of fluids used in practice, but also the fundamental flow problems - sociated with actual fluid machineries. Hence, the intended purpose of this book is to provide the fundamental and physical aspects of fluid mechanics and to develop engineering practice for fluid machineries. The subject of fluid engineering is most often approached at the senior undergraduate or postgraduate level of study. At this stage, the student or practical engineer is assumed to already have a basic mathematical ba- ground of vector and tensor analysis with a fair understanding of elem- tary fluid mechanics, such as Bernoulli equation, potential flow, and Poiseuille flow.